ESENSIALITAS HOME VISIT DALAM PENDIDIKAN - Yaqien, Nurul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
Each education institute has a great longing to be able to conduct all education programs thoroughly. The desire to do the whole brings in the school endeavor that is how to create favorable situation between schools and students’ participant. The aim in doing close relationship between school and students’ participant is to give more comprehension for them in school life. Home visit is one of the school programs whose enormous effect in attempting school programs. It does not only overcome the students’ difficulty or achievement of learning but also has a function as offering school programs which is necessary participation or involvement of students’ participant and people in the society to accomplish school programs well.Keyword: Home Visit, development, and Education